Culture vs. Civilisation dans les « voyages en France » de Stendhal : maltraités de l’Atlantique Nord et union pour la Méditerranée - Lévêque, Laure (Babel, 2015)
While on the prolonged release from duty that he is granted between 1836 -1839, Stendhal, consul in Italy - the country of his heart - since 1830, rediscovers in his fatherland, France, a country utterly changed by the swerve in growth that has occurred since the July Monarchy. This is the real shock that his “journeys in France” testify to, when the journey of recognition is accompanied by the self-examination in which what he sees sends Stendhal back to the blind spot of his vision, of France and of the world. Upon revisiting France, Stendhal also revisits his axiological system, which brings him, between life study and fictional mediation, to a semantic separation between civilization and culture, which follows quite closely the separation of waters between the Mediterranean and the Atlantic. Au cours du long congé qu’il obtient de 1836 à 1839, Stendhal, consul en Italie – la patrie de son cœur – depuis 1830, redécouvre dans la mère patrie une France profondément transformée par le tournant de la croissance pris sous la monarchie de Juillet. C’est de ce véritable choc que témoignent les « voyages en France », où le voyage de reconnaissance s’accompagne d’un retour sur soi quand les choses vues renvoient Stendhal au point aveugle de sa vision, de la France et du monde. À revoir la France, Stendhal revoit aussi son système axiologique pour aboutir, entre étude sur le vif et médiation de la fiction, à un partage sémantique entre civilisation et culture qui suit assez fidèlement la ligne de partage des eaux entre Méditerranée et Atlantique.